Keefektifan Penggunaan Media Bildergechichte dalam Pembelajaran Keterampilan Menulis Bahasa Jerman - Ummami, Titah Arkanul; Santoso, Iman (Universitas Negeri Yogyakarta, 2025)
This study aims to determine the effectiveness of using Bildergeschichte media in learning German writing skills of XII grade students of SMA Negeri 3 Bantul. This research is a Quasi Experiment with One Group Pre-Test Post-Test Design. This study consists of two variables, namely the independent variable in the form of Bildergeschichte media (X) and the dependent variable in the form of German writing skills (Y). The population of this study were students of class XII SMA Negeri 3 Bantul. With the Purposive Sampling technique, the sample of this research was 35 students. The data in this study were obtained using a writing skill test. Data analysis used the Paired Sample T-Test test. The result of this study showed that the writing skill of the students of grade XII SMA Negeri 3 Bantul was better after using Bildergeschichte media than when not using Bildergeschichte media. The use of Bildergeschichte media is effective in learning German writing skills of 12th-grade students of SMA Negeri 3 Bantul. Keywords: German, Bildergeschichte, Media, Writing Skills